Tourist motivation to consume Pulau Pinang local food / Norliana Hashim...[et al] - Hashim, Norliana; Kamarulzaman, Wan Dzafarul Ariff; Mohamed Idris, Aida Khalida; Salleh, Rashid (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
This paper presents the finding of a study that identifies the most influential factor among local tourists to consume Pulau Pinang’s food. Data collection was done in numerous tourist attraction spots in Pulau Pinang. A total 98 respondents were selected for this study, represented the local tourists who traveled to Pulau Pinang. Motivational factors included in this study are exciting experience, escape from routine, health concern, cultural experience. The finding shows that the most influential motivational factor is the cultural experience. It could be said that, the major reason for tourist to consume Pulau Pinang food is the cultural experience that they encounter during the consumption of the foods. It also shows that people engage with food tourism in Pulau Pinang to experience the local culture. The findings of the study can be used by the state’s tourism agencies to strengthen the efforts to develop and promote the food culture of Pulau Pinang hence, increasing the tourism value of the state.